Polyvictimization, Psychological Distress, and Trauma Symptoms in College Men and Women. Issue 2 (6th July 2019) - Elliott, Ann N.; Faires, Alyson; Turk, Rachel K.; Wagner, Lora C.; Pomeroy, Brianna M.; Pierce, Thomas W.; Aspelmeier, Jeffery E.
Abstract : This study examined the relationship between polyvictimization, psychological distress, and trauma symptoms in college men and women. Childhood victimization was common among participants. Regression analyses revealed that polyvictimization (i.e., high cumulative levels of victimization) is a better predictor of psychological distress and trauma symptoms than is any individual category of victimization (i.e., sexual, physical, peer/sibling, child maltreatment, witnessing/indirect, or property crime). Gender did not moderate the relation between victimization and distress and trauma symptoms. Implications for counselors are discussed.